FUNCTIONS AND ACTIVITIES OF THE CONTROLLERS DEPARTMENT. - Elliott, V. L. (The Accounting Review, 1940)
Development of the controllership functions, and position, as it is found today in American business, undoubtedly can be traced to the official Comptroller in Government posts, performing duties prescribed by law, in an effort to see to it that only appropriated funds were disbursed and for the purpose intended. This Government function came over into business as business units grew in size. Consequently, the position of "Comptroller" was found first in large concerns, such as railroads, mines, and large manufacturing establishments, many of which have had that office for forty to fifty years. A good controller is a service man, and must be a good salesman to sell the services of his department to the heads of the various operating departments. The most important function of a controller is that of interpretation of financial statements and other figures to the executives. It is amazing how some executives shun figures, especially a large sheet of figures. Therefore, it is frequently necessary to put important financial facts in story form with a punch to it.